Observaciones sobre la estrategia para el combate del empleo no registrado en la Argentina - Dalponte Roibás, Federico Nahuel (2015)
Analysis of Argentinian legislation about business activity regulation, control and punishment in matters of unregistered work concerning the recent enactment of laws 26940 and 26941. Consideration about the results achieved since year 2003 and alternative proposals in view of the union representation at the workplace and the stability of the worker of the private sector